ANALISIS SEGMENTING, TARGETING, POSITIONING PRODUK ( Kajian pada Kopi Bali Banyuatis) - Ni Ketut Lasmini; Sagung Mas Suryaniadi (Forum Manajemen STIMI Handayani Denpasar, 2013)
A company can not serve all customers in the vast market. It should observe themarket segment it can serve most effectively. A marketer should perform a strategyof 3 (three) major steps; identify and classify different customers (segmenting);choose one or more market segment to approach (targeting); and to make image oropinion and to communicate the major benefit to the customers that distinguish it tothe other (positioning). And this research aims to formulate a particular marketingstrategy; which consist of segmenting, targeting and positioning of “ Kopi BubukBali Banyuatis” The study was done in Denpasar, 140 sample was taken usingnon probability random sampling method, accidentally. Ordinal data 1 to 5 Likertscale was taken using questionnaire, transformed into interval data using IntervalSuccessive Method. The market segment of Kopi Banyuatis was formulated basedon the analysis of consumers behaviour and psychographic using Cluster Analysiswith K- Mean Cluster, result 3 clusters that are cross-tabulated with demographicvariable to obtain segmented consumer’s profile. The computer software SPSSVer 13.0 and Microsoft Excel-XP were used to assist all calculation steps in theanalysis. The output are: Segment-1, 42,9%, frequent consumption level, readinessto buy is high because they understand the product, positive attitude toward theproduct and its benefit. In terms of psychographic, segment-1 are active, modern,optimistic and secure.Various income, from low into high class. Potential as maintarget of the market. Segment-2, 35,7%, infrequent consumption level, moderate inreadiness to buy, positive attitude toward the product and its benefit. Psychographic:simple, optimistic. Potential as market target next to segment-1. Segment-3, 21,4%,consumption level rare, readiness to buy low, negative toward product and its benefit.Psychographic: logic, normative, homebody. Less potential as market target. Basedon the market size, structure, and the goal and capacity of the company , segment-1choosen as the target of the company. Product positioning on customers head andtheir perception are mapped using Correspondent Analysis and Multi DimensionalScaling (MDS). It shows that Kopi Banyuatis is in tight competition with Kopi BolaDunia regarding quality, discount, gift, and product diversity. Its advantages in quality, discount, gifts and product diversity will not be effective in the long run, because Kopi Banyuatis could easily imitate by its competitors. That’s why itsmarketing mix strategy upon the choosen segment, and product positioning shouldbe adjusted. Outstanding packaging will distinguish it from others. Various taste forthose who always like to try new product, and equal price for the middle-low classconsumers should be considered. Outstanding outlets make them easily seen by thecustomers and other promotion mix through advertising, sales promotion, publicrelations and personal selling should also be considered.